Alcohol Dehydrogenases as Catalysts in Organic Synthesis - de Miranda, Amanda Silva; Milagre, Cintia D. F.; Hollmann, Frank (Frontiers in Catalysis, 2022)
Alcohol dehydrogenases (ADHs) have become important catalysts for stereoselective oxidation and reduction reactions of alcohols, aldehydes and ketones. The aim of this contribution is to provide the reader with a timely update on the state-of-the-art of ADH-catalysis. Mechanistic basics are presented together with practical information about the use of ADHs. Current concepts of ADH engineering and ADH reactions are critically discussed. Finally, this contribution highlights some prominent examples and future-pointing concepts.